The language of performativity? A content analysis concerning differing constructions of leadership for secondary school PE departments. (27th May 2017) - Williams, Gareth
ABSTRACT: The aim of this paper was to analyse how teachers and government may differ in their views regarding the qualities required to be an effective middle manager with responsibility for Physical Education (PE). Lines of inquiry were based upon the practices associated with a performative work culture and how this has affected teacher language. There is a perception that Heads of Physical Education (HoPE) could possibly hold different views to those espoused by government. A content analysis was used to research differences between the language used by HoPE in the form of questionnaire responses and that used by government through OFSTED publications. An analysis of job adverts for middle management positions in PE was also undertaken to provide an extra dimension for comparison. Results showed that OFSTED documents reflecting government ideology used a language of performativity to describe leadership characteristics at a higher rate than that used by HoPE who revealed a preference for more personal, human attributes. However, both the HoPE responses and the school job adverts did use some performative language. A Foucauldian analysis of these findings suggested that middle managers, in particular, may be reluctantly using performative language to 'play the game' within differing power networks in order to claim limited resources.